A peculiar new Oriental genus of Drymini (Hemiptera: Heteroptera: Rhyparochromidae) - Kondorosy, Előd; Kovács, Szilvia (Zootaxa, 2026)
Formidrymus malayus, gen. et sp. nov. (Hemiptera: Heteroptera: Rhyparochromidae: Rhyparochrominae: Drymini) is described based upon specimens from Indonesia, Malaysia and Singapore. The systematic position of the genus and the potentially related genera are discussed, especially the superficially similar Fontejanus Breddin, 1903, a rhyparochromine genus of uncertain tribal placement.